(untitled) (Bioscience Journal, 2017)
Two renal arteries supply the human kidneys: one to the right kidney and another to the left kidney, both branches of the abdominal aortic. Renal artery duplication is an anatomical variation, which is a normal flexibility of the topography and morphology in body structures. Functionally, it does not impair the body, as the blood supply is vital to tissue survival. In this context, the case study has great importance, once knowing the variations of the renal vessels assist when structuring surgeries and radiological studies in humans. Variations in vascular anatomy are often found in humans. Several authors characterize it: the prevalence of multiple vessels occurs in approximately 20-50% of cases. This is an observational study; we aimed to describe the anatomical variations concerning the duplicity of the renal artery in human cadavers, focusing on possible implications to clinical and surgical procedures. We dissected and analyzed four urinary block systems in adult cadavers, male, with focus on the vascularization. In these, two right kidneys present double renal arteries. Thus, we can infer that this knowledge can be used to improve surgical interventions, such as transplants.